2005
DOI: 10.1590/s0100-879x2005000300010
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerosis in aged mice over-expressing the reverse cholesterol transport genes

Abstract: We determined whether over-expression of one of the three genes involved in reverse cholesterol transport, apolipoprotein (apo) AI, lecithin-cholesterol acyl transferase (LCAT) and cholesteryl ester transfer protein (CETP), or of their combinations influenced the development of diet-induced atherosclerosis. Eight genotypic groups of mice were studied (AI, LCAT, CETP, LCAT/AI, CETP/AI, LCAT/ CETP, LCAT/AI/CETP, and non-transgenic) after four months on an atherogenic diet. The extent of atherosclerosis was asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
0
6
0
1
Order By: Relevance
“…As mice are naturally resistant to atherosclerosis, the average lesion size in the animals was small, with a maximum lesion size of ‫ف‬ 25,000 m 2 in the human LCAT transgenic mice with 240 copies of the transgene. In the Francone mice ob the FVB background, a ‫ف‬ 2.5-fold nonsignifi cant increase in lesion size was observed ( 119 ). In the presence of human apoAI, however, a signifi cant 3.4-fold increase in lesion size was found.…”
Section: Lcat and Atherosclerosis In Lcat Knockout Mouse Modelsmentioning
confidence: 94%
See 1 more Smart Citation
“…As mice are naturally resistant to atherosclerosis, the average lesion size in the animals was small, with a maximum lesion size of ‫ف‬ 25,000 m 2 in the human LCAT transgenic mice with 240 copies of the transgene. In the Francone mice ob the FVB background, a ‫ف‬ 2.5-fold nonsignifi cant increase in lesion size was observed ( 119 ). In the presence of human apoAI, however, a signifi cant 3.4-fold increase in lesion size was found.…”
Section: Lcat and Atherosclerosis In Lcat Knockout Mouse Modelsmentioning
confidence: 94%
“…Furthermore, it has to be taken into account that cholate-containing diets can have detrimental effects on liver function. For example, in the study of Berti and colleagues using the Francone human LCAT transgenic mice, it was clearly stated that 19% of the mice died during the 16-week dietfeeding period and that at the end of the study, all mice showed signals of hepatic steatosis and had gall bladders full of gallstones ( 119 ).…”
Section: Lcat and Atherosclerosis In Human Lcat Transgenic Mouse Modelsmentioning
confidence: 99%
“…Atherosclerosis extent was strongly and directly proportional to the ratio (LDL-C ϩ VLDL-C)/HDL-C. In the setting of human LCAT over-expression, CETP actually decreased atherosclerosis (137). Thus, relevance to human is unclear.…”
Section: Cetpmentioning
confidence: 99%
“…Several studies using CETP transgenic models showed that CETP expression could be either pro-or anti-atherogenic. CETP expression plays a protective role in conditions such as hypertriglyceridemia (20), overexpression of LCAT (21,22), excess of apo B combined with lipoprotein lipase deficiency and diabetes (23), diabetes and obesity (24), castration (25,26), and SRBI deficiency (27). Conversely, CETP exacerbates atherosclerosis when expressed in very high levels (seven-fold simian plasma levels) (28), in severe hypercholesterolemia due to the deletion of LDL receptors or apo E genes (29) and in hypertensive rats (30).…”
Section: Cetp and Atherogenesismentioning
confidence: 99%
“…This role of CETP seems to be relevant since CETP deficient patients have higher levels of oxLDL (56). In addition, ovariectomized CETP transgenic mice present levels of anti-oxLDL antibodies that are lower than their CETP non-expressing littermates (22). Protection against lipoprotein oxidation is a well-known anti-atherogenic action of estrogen (57).…”
Section: Protection Against Lipoprotein Oxidationmentioning
confidence: 99%